2014
DOI: 10.4047/jap.2014.6.6.498
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for dental implant nanosurface modifications

Abstract: PURPOSEDental implant has gained clinical success over last decade with the major drawback related to osseointegration as properties of metal (Titanium) are different from human bone. Currently implant procedures include endosseous type of dental implants with nanoscale surface characteristics. The objective of this review article is to summarize the role of nanotopography on titanium dental implant surfaces in order to improve osseointegration and various techniques that can generate nanoscale topographic fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Various studies have been carried out in this area [ 78 80 ]. In the typical procedure, surface contaminants (hydrocarbons) are removed by decomposition and photocatalysis through UV rays [ 81 ]. This helps to improve the wettability of the implant surface and results in more cases of successful osseointegration [ 82 ].…”
Section: Sources Of Ros In Dentistrymentioning
confidence: 99%
“…Various studies have been carried out in this area [ 78 80 ]. In the typical procedure, surface contaminants (hydrocarbons) are removed by decomposition and photocatalysis through UV rays [ 81 ]. This helps to improve the wettability of the implant surface and results in more cases of successful osseointegration [ 82 ].…”
Section: Sources Of Ros In Dentistrymentioning
confidence: 99%
“…[11] Biologically Active Drugs Incorporated Dental Implants Incorporation of some osteogenic and antiresorptive drugs, such as bisphosphonate onto the implant surface, can be used appropriately in clinical cases with inadequate bone support. [2] Bisphosphonates Bisphosphate-loaded implant surfaces have been reported to have improved implant osseointegration.…”
Section: Magnetron Sputteringmentioning
confidence: 99%
“…Recently, numerous methods have been used to modify implant surfaces to enhance the speed of bone healing [1][2][3][4][5][6][7][8][9][10]. It was found that osseointegration could be effectively promoted by surface modification [1,2,4,11,12].…”
Section: Introductionmentioning
confidence: 99%